Faktor yang Berhubungan dengan Kejadian Gagal Ginjal Kronik Pada Pasien Hemodialisa di RS. Pertamina Bintang Amin Bandar Lampung - Nopriani Nopriani; Eka Yudha Chrisanto; Dewi Kusumaningsih (Universitas Malahayati Lampung, 2024)
ABSTRACT The incidence of chronic kidney disease is influenced by many factors. There needs to be a role for risk factors together (common underlying risk factor) for the occurrence of chronic kidney disease. for Pertamina Bintang Amin Hospital cases of kidney failure itself, namely 189 cases in October 2022, 209 cases in November 2022, 223 cases in December 2022 in a month and for patients undergoing hemodialysis therapy there are 79 patients in November, 84 patients in December In 2022, the trend of chronic kidney disease in hospitals will continue to increase. Pertamina Bintang Amin. Know The Factors Associated With The Incidence Of Chronic Renal Failure In Hemodialysis Patients At Hospital Pertamina Bintang Amin Bandar Lampung in 2023. This type of quantitative research with a cross sectional. This population is kidney failure patients totaling 84respondentsand the sample is total sampling. The sample of this study was 84 respondents according to predetermined inclusion criteria. The research instrument used a questionnaire. Analysis of the data used for analysis of variate frequency distribution and bivariate analysis using the chi square test. This study shows the frequency distribution of respondents having (70.2%) terminal renal failure, average age 56.89 years, most of the patients (54.8%) were male, (75%) yes, history of hypertension, (64.3%) yes history of DM, (59.5%) yes history of UTI, (69%) no history of kidney stones. The relationship between the incidence of kidney failure and hypertension (p value 0.001), the incidence of kidney failure and DM (p value 0.006), the incidence of kidney failure and UTI (p value 0.502), the incidence of kidney failure and kidney stones (p value 0.363). There is a relationship between a history of hypertension and DM with the Incidence of Chronic Kidney Failure in Hemodialysis Patients at RSPBA. There is no relationship between history of ISK and kidney stones. Chronic Kidney Failure in Hemodialysis Patients at RSPBA. Keywords: Patients, Chronic Kidney Disease ABSTRAK Kejadian penyakit ginjal kronik banyak dipengaruhi oleh berbagai faktor. Perlu adanya peran faktor risiko secara bersama-sama (common underlying risk factor) untuk terjadinya penyakit ginjal kronik dan untuk Rumah Sakit Pertamina Bintang Amin kasus gagal ginjal sendiri yaitu 189 kasus dibulan oktober 2022, dibulan 209 kasus di bulan november 2022, 223 kasus di bulan desember 2022 dalam sebulannya dan untuk pasien yang menjalani terapi hemodialisa ada 79 pasien dibulan november, 84 pasien dibulan desember 2022 dengan begitu maka terus meningkatnya tren penyakit penyakit ginjal kronik yang ada di RS. Pertamina Bintang Amin. Diketahui Faktor - Faktor Yang Berhubungan Dengan Kejadian Gagal Ginjal Kronik Pada Pasien Hemodialisa Di RS. Pertamina Bintang Amin Bandar Lampung Tahun 2023. Jenis penelitian kuantitatif dengan pendekatan cross sectional. Populasi ini adalah pasien gagal ginjal yang berjumlah 84 responden dan sampelnya total sampling. Sampel penelitian ini berjumlah 84 responden sesuai dengan kriteria inklusi yang telah ditetapkan. Instrumen penelitian ini menggunakan kuesioner. Analisa data yang digunakan untuk analisa variat distribusi frekuensi dan analisa bivariat menggunakan uji chi square. Dalam penelitian ini menunjukkan distribusi frekuensi responden memiliki (70,2%) gagal ginjal terminal,rata-rata usia 56,89 tahun, sebagian besar pasien (54,8%) laki-laki, (75%) ya, riwayat hipertensi, (64,3%) ya riwayat DM, (59,5%) yariwayat ISK, (69%) tidakriwayat batu ginjal. Hubungan antara kejadian gagal ginjal dan hipertensi (p value 0,001), kejadian gagal ginjal dan DM (p value 0,006), kejadian gagal ginjal dan ISK (p value 0,502), kejadian gagal ginjal dan batu ginjal (p value 0,363). Ada hubungan antara faktor riwayat hipertensi dan DM dengan Kejadian Gagal Ginjal Kronik Pada Pasien Hemodialisa di RSPBA. Tidak ada hubungan faktor riwayat ISK dan batu ginjal dengan Kejadian Gagal Ginjal Kronik Pada Pasien Hemodialisa di RSPBA. Kata Kunci: Pasien, Gagal Ginjal Kronik